African Lace-Bark in the Caribbean: The construction of race, class, and gender - Buckridge, Steeve O (Bloomsbury Publishing Plc, 2016)
This study focuses on the making of African bark-cloth in the Caribbean and the use of plant fibers and pigments in the production and care of clothing for members of the colonized population. The material artifact of interest in this study is lace-bark, a form of bark-cloth, obtained from the bark of the lagetto tree found only in Jamaica, Cuba and Haiti. The fibres of the lagetto bark were removed by hand and dried, and the end result resembled fine lace or linen that was used by enslaved and freed women in Jamaica to make clothing as well as a substitute for manufactured lace. Although lace-bark is derived from the bark of a tree, it is different from other forms of bark-cloth. For instance, unlike most bark-cloth, the bark of the lagetto tree was not beaten into malleable cloth. The scientific name for the lace-bark tree is Lagetta lagetto; however, common names and spelling vary across regions. The author argues that a vibrant cottage industry based on African bark-cloth and lace-bark developed in Jamaica in response to economic conditions, and the insufficient clothing enslaved Africans received from their enslavers. Women dominated this industry and it fostered a creative space that allowed them to be expressive in their dress and simultaneously to escape, at least temporarily, the harsh realities of the plantation. The subjects of this study are women of African ancestry living in Jamaica from the seventeenth to the early twentieth century. By the late seventeenth century, a bark industry had developed in Jamaica that was responsible for producing exquisite bark material that was widely popular. The laghetto tree was known in Cuba as the Daguilla, and in Haiti as bois dentelle.